Endothelial Cx40 limits myocardial ischaemia/reperfusion injury in mice. (17th March 2014) - Morel, Sandrine; Braunersreuther, Vincent; Chanson, Marc; Bouis, Diane; Rochemont, Viviane; Foglia, Bernard; Pelli, Graziano; Sutter, Esther; Pinsky, David J.; Mach, François; Kwak, Brenda R.
Abstract: Aims: Gap junctions are indispensable for the function of heart and blood vessels by providing electrical coupling and direct cell-to-cell transfer of small signalling molecules. Gap junction channels between neighbouring cells are composed of 12 connexins (Cx). Changes in Cx43 expression, localization, and channel properties in cardiomyocytes contribute to infarction and reperfusion injury of the heart. It is increasingly recognized that deleterious consequences of ischaemia/reperfusion (IR) are modulated by the inflammatory response and endothelial function. The role of the endothelial connexins, i.e. Cx40 and Cx37, in cardiac IR injury is, however, not known. Methods and results: Following 30 min ischaemia and 24 h reperfusion, we found a significant increase in myocardial infarct size in mice with endothelial-specific deletion of Cx40 (Cx40del), but not in Cx37-deficient mice. The cardioprotective effect of endothelial Cx40 was associated with a decrease in neutrophil infiltration. Moreover, beneficial effects of endothelial Cx40 were not observed in isolated Langendorff-perfused hearts, suggesting direct involvement of endothelial–leucocyte interactions in the cardiac injury. Single-dose administration of methotrexate, a CD73 activator, reduced infarct size and neutrophil infiltration into the infarcted myocardium in Cx40del but not in control mice. Similar to Cx40del mice, CD73-deficient mice showed increased sensitivity to cardiac IR injury, which could not be conversed by methotrexate. Conclusion: Endothelial Cx40, but not Cx37, is implicated in resistance of the heart to IR injury by activation of the CD73 pathway. Thus, the Cx40–CD73 axis may represent an interesting target for controlling reperfusion damage associated with revascularization in coronary disease.